2020
DOI: 10.1371/journal.pone.0226621
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a laboratory-based wheelchair castor testing protocol using community data

Abstract: Wheelchair castors fail frequently causing physical, social and economic consequences for wheelchair users. These failures occur in spite of established wheelchair test methods and regulations, suggesting that the existing tests may not be sufficient to screen poorly designed castors. An expert stakeholder group, convened by the International Society of Wheelchair Professionals (ISWP), noted castor failures as a high priority and recommended that a new castor testing system should be developed. In a previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Casters undergo corrosion exposure in a salt fog chamber followed by shock and abrasion testing on turntable equipment with multiple bumps of varying heights. 21 One of the caster testing studies showed that testing affected the rolling of axle bearings and turning of stem bearings of casters, similar to what was observed in the community. 21 These observations combined with expert feedback from the International Society of Wheelchair Professionals (ISWP) Standards Working Group provided the motivation for specifically investigating the effect of environmental factors on RR in this study.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Casters undergo corrosion exposure in a salt fog chamber followed by shock and abrasion testing on turntable equipment with multiple bumps of varying heights. 21 One of the caster testing studies showed that testing affected the rolling of axle bearings and turning of stem bearings of casters, similar to what was observed in the community. 21 These observations combined with expert feedback from the International Society of Wheelchair Professionals (ISWP) Standards Working Group provided the motivation for specifically investigating the effect of environmental factors on RR in this study.…”
Section: Introductionmentioning
confidence: 58%
“…Accelerations due to road shocks were translated to durability test equipment with appropriate slat height. 21 Number of road shocks observed during the testing were extrapolated to two years of shock exposure since majority of casters fail within 2 years. Testing caster models with a combination of shocks, abrasion and corrosion reproduced real world caster failures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations